2020
DOI: 10.1111/jnc.14969
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box O3a requires BAF57, a subunit of chromatin remodeler SWI/SNF complex for induction of p53 up‐regulated modulator of apoptosis (Puma) in a model of Parkinson’s disease

Abstract: Parkinson's disease (PD) results from the selective loss of dopaminergic neurons of substantia nigra pars compacta region of the midbrain. It has been reported that the transcription factor forkhead Box O3a (FoxO3a) is activated and induces pro‐apoptotic protein such as Bcl‐2‐interacting mediator of cell death (BIM) and p53 up‐regulated modulator of apoptosis (PUMA) in variety of neuron death paradigms. Activity of FoxO3a is governed by its post‐translational modifications which control its subcellular localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Using standard in vitro models of PD, our uorescent imaging and ow cytometry-based experiments respectively showed that miR-128 over-expression could attenuate the production of mitochondrial superoxide radicals as well as prevent cells from 6-OHDA mediated death. Now, earlier report from our lab had shown that 6-OHDA can induce neuronal apoptosis via activation of a transcription factor called FoxO3a (Sanphui et al 2020). Keeping that in mind, we explored the implications of miR-128 in apoptotic pathways and its effect on FoxO3a activation.…”
Section: Discussionmentioning
confidence: 99%
“…Using standard in vitro models of PD, our uorescent imaging and ow cytometry-based experiments respectively showed that miR-128 over-expression could attenuate the production of mitochondrial superoxide radicals as well as prevent cells from 6-OHDA mediated death. Now, earlier report from our lab had shown that 6-OHDA can induce neuronal apoptosis via activation of a transcription factor called FoxO3a (Sanphui et al 2020). Keeping that in mind, we explored the implications of miR-128 in apoptotic pathways and its effect on FoxO3a activation.…”
Section: Discussionmentioning
confidence: 99%
“…MYC and PI3K-AKT signaling cooperatively repress FOXO3a-dependent PUMA expression [ 53 ]. However, chromatin remodeler Brg-associated factor 57 (BAF57), a subunit of SWItch/sucrose non-fermentable (SWI/SNF), executes neuron death in FoxO3a-mediated PUMA expression in cellular models of Parkinson’s disease (PD) [ 54 ]. In addition, autophagy inhibition increases the levels of FOXO3a transcription factor, and promotes PUMA upregulation, thereby increasing apoptosis [ 55 ].…”
Section: Puma-mediated Signaling Pathwaysmentioning
confidence: 99%
“…TRIB3/TRB3 (a target of CHOP) is induced later than CHOP during ER stress [ 98 ], and it can promote PUMA expression in a FOXO3a-dependent manner through the dephosphorylation of AKT in PC-12 cells [ 98 ]. BAF57 executes neuron death in FoxO3a-mediated PUMA expression in cellular models of PD [ 54 ].…”
Section: Puma Deficiency Significantly Protects Neurons From Er-stress-induced Apoptosis For Neurodegenerative Diseasesmentioning
confidence: 99%
“…SIRT1 also is closely associated with the mammalian forkhead transcription proteins [24,55,[193][194][195][196][197]. The induction of autophagy relies upon mammalian FOXO proteins of the O class that have an important relationship to neurodegenerative disorders [40,162,187,198,199]. For example, central nervous system myelination involving oligodendrocyte progenitor cells is believed to be controlled through FoxO1 transcription factors [200] that may impact disease such as multiple sclerosis [201].…”
Section: Circadian Clock Genes and The Silent Mating Type Information Regulation 2 Homolog 1 (Saccharomyces Cerevisiae) (Sirt1)mentioning
confidence: 99%